Social Violence in the Prehispanic American Southwest - Crown, Patricia L.; Nichols, Deborah L. (Book collections on Project MUSE., 2008)
"Deborah L. Nichols and Patricia L. Crown have gathered nine contributions from a variety of disciplines to examine social violence in the prehispanic American Southwest. Not only offering specific case studies but also delving into theoretical aspects, this volume looks at archaeological interpretations, multidisciplinary approaches, and the implications of archaeological research for Native peoples and how they are impacted by what archaeologists say about their past."--Jacket.